Immunohistochemical analysis of the gingiva with periodontitis of type I plasminogen deficiency compared to gingiva with gingivitis and periodontitis and healthy gingiva. (December 2016) - Kurtulus Waschulewski, Idil; Gökbuget, Aslan Y.; Christiansen, Nina M.; Ziegler, Maike; Schuster, Volker; Wahl, Gerhard; Götz, Werner
Highlights: Type I plasminogen deficiency is an uncommon chronic inflammation of mucous membranes. Fibrin clearance is disturbed in this entity. Plasmin(ogen)-independent enzymatic fibrin clearance through elastase, MMP-3, MMP-7 have been shown in this study. The exact pathomechanism of this entity needs to be determined. Abstract: Objective: Type I plasminogen deficiency (Plgdef) is an uncommon chronic inflammation of mucous membranes. Gingival enlargements usually proceed with progressive periodontal destruction and tooth-loss. Plasmin(ogen)-independent enzymatic mechanisms for fibrin clearance have already been discussed in the literature. Our primary objective was to verify, immunohistochemically, the occurrence of different enzymatic factors involved in tissue breakdown of inflamed compared to healthy gingiva. Secondly, we tried to find out, if these patients have a similar microbiological profile to the patients with known gingivitis and periodontitis. Materials and methods: Immunohistochemical analysis of enzymes elastase, plasminogen (plg), cathepsin G, matrix-metalloproteinase (MMP)-3 and MMP-7 and of glycoprotein fibrinogen were performed with gingival tissues from 3 healthy controls, 8 patients with Plgdef and 3 patients with gingivitis and periodontitis. Furthermore, plaque from 5 patients with plasminogen deficiency were also obtained to determine the microbiological profile. Results: Significantly high numbers of elastase positive leukocytes were detected in all samples. Staining for MMP-3 and MMP-7 was seen in samples with gingivitis and periodontitis with a stronger staining in samples with periodontitis by Plgdef. Fibrinogen was detectable in all samples. Staining for plg was stronger in samples with periodontitis than in other samples. Staining for cathepsin G was weak in gingivitis and periodontitis. Subgingival microbial flora showed elevated colony forming units of Prevotella intermedia/nigrescens, Fusobacterium spp., Eikenella corrodens, Porphyromonas gingivalis and viridans streptococci . Conclusion: Strong staining of elastase, MMP-3 and MMP-7 and weak staining of plg in Plgdef samples supports the plasmin(ogen) – independent fibrin clearance. Similar subgingival microbiological flora was observed in periodontitis with Plgdef as in other periodontal diseases. Further investigations should determine the exact pathomechanism and focus on effective treatment methods of this entity.